2017
DOI: 10.3389/fpls.2017.01693
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of NPR1 in Brassica juncea Confers Broad Spectrum Resistance to Fungal Pathogens

Abstract: Brassica juncea (Indian mustard) is a commercially important oil seed crop, which is highly affected by many biotic stresses. Among them, Alternaria leaf blight and powdery mildew are the most devastating diseases leading to huge yield losses in B. juncea around the world. In this regard, genetic engineering is a promising tool that may possibly allow us to enhance the B. juncea disease resistance against these pathogens. NPR1 (non-expressor of pathogen-related gene 1) is a bonafide receptor of salicylic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 74 publications
2
37
0
Order By: Relevance
“…NPR1 is thought to be the master regulator of SAR because loss‐of‐function npr1 plants are almost completely defective in establishing SAR in response to pathogen infection (Pajerowska‐Mukhtar, Emerine, & Mukhtar, ). In addition, npr1 mutants are impaired in some R gene‐mediated resistance, with enhanced susceptibility to virulent pathogens (Pajerowska‐Mukhtar et al, ), whereas NPR1 overexpression in Arabidopsis plants and several crops significantly increased disease resistance to a broad range of pathogens including fungus, bacterium, and nematode (Ali et al, ), indicating NPR1 is also involved in local defence response, PAMP‐triggered immunity and effector‐triggered immunity. In our work, in npr1‐1 mutant, cold stress could still activate the immunity and expression of some key SA pathway genes (as tested for PR2 , PR5 , AZI1 , and EARLI1 ; Figures and ) but less strongly than in cold‐stressed wild type plants, indicating that NPR1 is partially required for cold activation of disease resistance, and there exists an NPR1 ‐independent SA pathway in cold activated immunity, similar to previous evidence showing that there is an NPR1 ‐independent SA pathway in plant defence response.…”
Section: Discussionmentioning
confidence: 99%
“…NPR1 is thought to be the master regulator of SAR because loss‐of‐function npr1 plants are almost completely defective in establishing SAR in response to pathogen infection (Pajerowska‐Mukhtar, Emerine, & Mukhtar, ). In addition, npr1 mutants are impaired in some R gene‐mediated resistance, with enhanced susceptibility to virulent pathogens (Pajerowska‐Mukhtar et al, ), whereas NPR1 overexpression in Arabidopsis plants and several crops significantly increased disease resistance to a broad range of pathogens including fungus, bacterium, and nematode (Ali et al, ), indicating NPR1 is also involved in local defence response, PAMP‐triggered immunity and effector‐triggered immunity. In our work, in npr1‐1 mutant, cold stress could still activate the immunity and expression of some key SA pathway genes (as tested for PR2 , PR5 , AZI1 , and EARLI1 ; Figures and ) but less strongly than in cold‐stressed wild type plants, indicating that NPR1 is partially required for cold activation of disease resistance, and there exists an NPR1 ‐independent SA pathway in cold activated immunity, similar to previous evidence showing that there is an NPR1 ‐independent SA pathway in plant defence response.…”
Section: Discussionmentioning
confidence: 99%
“…AeNPR1a transcription was induced not only by treatment with SA or MeJA but also by pathogen infection, which may be associated with the presence of phytohormone and defense responsive elements in the promoter. In contrast, the expression of BjNPR1 in mustard was not altered after MeJA treatment (Ali et al, 2017). The discrepancy could be attributed to variation of the mechanism of signal molecules in different species (Kunkel and Brooks, 2002;Caarls et al, 2015).…”
Section: Discussionmentioning
confidence: 85%
“…It has been previously reported that exogenous plant defense molecules, such as SA, JA, and so on, can induce expression of NPR1 or its homologous genes, to activate plant disease resistance responses (Kunkel and Brooks, 2002;Ali et al, 2017;Neeley et al, 2019). Here, the temporal expression profiles of AeNPR1a in leaves following treatment with SA, MeJA as well as infection with Psa, were analyzed by real-time qRT-PCR, respectively.…”
Section: Expression Analysis Of Aenpr1a In Different Tissues and In Rmentioning
confidence: 99%
“…It was demonstrated that NPR1 serves as a coactivator of transcription, and mutants with defects in NPR1 fail to express several pathogenesis-related protein (PR) genes or develop SAR and are more prone to fungal and bacterial infections (Kinkema et al 2000, Ding et al 2018. In contrast, the overexpression of NPR1 in many species confers transgenic plants enhanced resistance to diverse pathogens (Chern et al 2001, Fitzgerald et al 2004, Makandar et al 2006, Sundaresha et al 2016, Ali et al 2017. Moreover, NPR1 is not only involved in the defense response but also in some other biological processes.…”
Section: Mulberry Plants Have Been Used Formentioning
confidence: 99%